The expression of human β-defensins (hBD-1, hBD-2, hBD-3, hBD-4) in gingival epithelia. (June 2016) - Li, Xinyi; Duan, Dingyu; Yang, Jingmei; Wang, Panpan; Han, Bo; Zhao, Lei; Jepsen, Soren; Dommisch, Henrik; Winter, Jochen; Xu, Yi
Graphical abstract: The peptide of hBD-1, hBD-2, hBD-3 and hBD-4 were expressed in human gingival epithelia. The expressions of peptide hBD-1, hBD-2 and hBD-3 in healthy gingiva were observed only in the cytoplasm. The expression of hBD-4 peptide was observed in the nucleus and cytoplasm. Comparison of the mRNA transcript (expressive) levels of hBD-1, hBD-2, hBD-3, and hBD-4 within the healthy group (A) and chronic periodontitis (CP) group (B). Significant differences were found by the Wilcoxon signed-rank-test: (A) p  < 0.01 for hBD-2: hBD-4 ( ) and p  = 0.004 for hBD-3: hBD-4 ( ); (B) p  < 0.01 for hBD-2: hBD-4 (∂) and p  < 0.01 for hBD-3: hBD-4 ( ). Highlights: HBD-4was first detected both in chronic inflamed and healthy gingiva. The mRNA relative expression of four β-defensins were analyzed in same sample. The peptide expression of hBD-4 was observed in the nucleus and cytoplasm, hBD-1, hBD-2 and hBD-3 were observed in the cytoplasm. Abstract: Objective: The aim of this study was to analyze and compare the expression patterns of human β-defensin-4 (hBD-4) with those of hBD-1, hBD-2, and hBD-3 in healthy and chronically inflamed gingival tissues. Materials and methods: A total of 96 gingival samples were collected, comprising 46 biopsies from chronic periodontitis (CP) patients and 50 from individuals with healthy tissue. Of these, 21CP and 21 healthy samples were used to examine the protein expression of the hBDs by immunohistochemistry. The remaining 25CP and 29 healthy tissue samples were subjected to real-time reverse transcription polymerase chain reaction to quantify the mRNA expression of the hBDs. Results: All four types of β-defensin peptides were confined to the gingival epithelia. The percentage of samples positive for hBD-4 mRNA was significantly lower than the percentages for the other three β-defensins, both in healthy ( p  = 0.003) and in inflamed ( p  = 0.030) gingiva. However, in the case of the relative mRNA expression levels, that of hBD-4 was significantly higher than the levels for hBD-2 (healthy group: p <  0.01; CP group: p <  0.01) and hBD-3 (healthy group: p  = 0.004; CP group: p <  0.01). Conclusions: Our study demonstrates differential expression of hBD-1, hBD-2, hBD-3, and hBD-4 in healthy and CP gingiva.